Review of Artemis Yagou’s Fragile Innovation: Episodes in Greek Design History - Plantzos, Dimitris (Historein, 2013)
Artemis Yagou Fragile Innovation: Episodes in Greek Design History North Charleston, SC: CreateSpace, 2011. 230 pp. Dimitris Plantzos University of Athens